Common Unfolding of Regular Tetrahedron and Johnson-Zalgaller Solid - Araki, Yoshiaki; Horiyama, Takashi; Uehara, Ryuhei (Journal of Graph Algorithms and Applications, 2016)
In this paper, we investigate the common unfolding between regular tetrahedra and Johnson-Zalgaller solids. More precisely, we investigate the sets of all edge developments of Johnson-Zalgaller solids that fold into regular tetrahedra. We show that, among 92 Johnson-Zalgaller solids, only J17 (gyroelongated square dipyramid) and J84 (snub disphenoid) have some edge developments that fold into a regular tetrahedron, and the remaining Johnson-Zalgaller solids do not have any such edge development.